2004
DOI: 10.1007/s00383-003-1097-z
|View full text |Cite
|
Sign up to set email alerts
|

Umbilicoplasty for large protruding umbilicus accompanying umbilical hernia: a simple and effective technique

Abstract: A large umbilical protrusion with redundant skin accompanying an umbilical hernia sometimes needs umbilicoplasty. Although several different techniques for making umbilical depression have been used, the results of the plastic surgery are sometimes unsatisfactory due to postoperative flattening or disappearance of the umbilical depression. To make a permanent umbilical depression that is cosmetically acceptable, we have modified the techniques. Umbilicoplasty was performed in 14 children whose ages ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…With the double half-cone umbilicoplasty, [11] after 3 cm of fascial defect, the cosmetic result will be discussed because the neo-umbilical rim will be too large. The technique of Ikeda et al [12] is adapted for UH that BD is between 2 and 2.5 cm; it cannot provide good result with what we call HUH. With HUH, even in Group 1, there will be an added scar, even with the "lazy M" and omega flaps.…”
Section: The Added Scarmentioning
confidence: 99%
“…With the double half-cone umbilicoplasty, [11] after 3 cm of fascial defect, the cosmetic result will be discussed because the neo-umbilical rim will be too large. The technique of Ikeda et al [12] is adapted for UH that BD is between 2 and 2.5 cm; it cannot provide good result with what we call HUH. With HUH, even in Group 1, there will be an added scar, even with the "lazy M" and omega flaps.…”
Section: The Added Scarmentioning
confidence: 99%
“…Some support umbilicoplasty to achieve an aesthetic repair. 51 Further study into the genetic mechanisms associated with the normal programmed umbilical closure may reveal additional novel approaches to the repair of these hernias.…”
Section: Umbilical Herniasmentioning
confidence: 99%
“…Some authors have reported modified techniques that can be used in patients with large umbilical hernia [1][2][3]. However, these techniques sometimes cause unsatisfactory results, particularly postoperative infraumbilical flattening and disappearance of the umbilical depression.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures are usually performed through a curved infraumbilical incision along the umbilical ring [1][2][3]. However, in cases of large umbilical hernia, these surgical techniques cannot diminish the diameter of the umbilicus, and unsatisfactory results are sometimes encountered, such as remnant of a large umbilical ring, postoperative flattening, or disappearance of the umbilical depression.…”
mentioning
confidence: 99%